2010
DOI: 10.1177/003335491012500411
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Elevated PTSD Risk in Firefighters Exposed to the World Trade Center Disaster: 2001–2005

Abstract: Elevated PTSD risk was associated with exposure to the WTC site as well as functional impairment, and remained largely unabated during the first four years of the study. Screening for elevated PTSD risk may be useful in identifying those who could benefit from interventions during long-term follow-up, as well as in the immediate aftermath of disasters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
127
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 46 publications
11
127
0
5
Order By: Relevance
“…It was also notable that mission duration was independently associated with difficulties relating to "Culture and Custom", "Infrastructure", and "Cooperation" during disaster relief missions, even after full adjustment. Our results corroborate previous findings (Berninger et al, 2010;Brackbill et al, 2009) suggesting an association between the negative experiences of relief workers and the length of the mission. By providing evidence on the association between the length of the mission and difficulties in disaster relief, our findings suggest that relief organizations should enhance assistance for relief workers, focusing on each HADS subscale depending on mission duration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was also notable that mission duration was independently associated with difficulties relating to "Culture and Custom", "Infrastructure", and "Cooperation" during disaster relief missions, even after full adjustment. Our results corroborate previous findings (Berninger et al, 2010;Brackbill et al, 2009) suggesting an association between the negative experiences of relief workers and the length of the mission. By providing evidence on the association between the length of the mission and difficulties in disaster relief, our findings suggest that relief organizations should enhance assistance for relief workers, focusing on each HADS subscale depending on mission duration.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, relief workers' negative experiences are likely to vary according to mission duration. Some studies have indicated that prolonged time spent at a domestic disaster site significantly promoted distress (Berninger et al, 2010;Brackbill et al, 2009), while other studies have found no significant association between the number of days spent at a domestic disaster site and psychological distress (Bowler et al, 2012;Dobashi et al, 2014). However, little is known about the association between the length of the mission on an overseas disaster site and the negative experiences of disaster relief workers.…”
Section: Introductionmentioning
confidence: 99%
“…Our screening tool for assessment of PTSD was based on the PCL-17, but the wording of questions and the answer formats were slightly different. However, this modifi ed version had been used previously in the FDNY population, 8,34,35 and was found to agree well with the PCL-17. 24 We believe that a considerable strength of this study is our use of the same tool and method of administration at both time points, and reported prevalence estimates that were consistent with other studies.…”
Section: Discussionmentioning
confidence: 60%
“…Within-factor paths across Time 1 and Time 2 CFA models were tested (as in Berninger et al, 2010). Each of the ASI-3 factor items exhibited high levels of stability as estimated by the values of the within-factor paths across Time 1 and Time 2 for the CFA.…”
Section: Resultsmentioning
confidence: 99%